(untitled) (TAMADDUN NURI JURNALI, 2024)
Animalistics studies the linguistic aspects of communication between different species of animals or between humans and animals. This is an interesting line of research that involves the study of sounds, gestures, facial expressions, symbols and other forms of communication used by animals to convey information. In the context of animalistics, this article examines how ideas about animals influence the structure of language and vice versa, how language shapes our understanding of animals.